Swim, Mo, swim! - Adler, David A.; Ricks, Sam (Penguin Young Readers, an imprint of Penguin Random House LLC, 2020)
On Field Day, Mo swims a lot faster than he knew he could, not because his team might win but because a fish keeps nibbling his toe.
Guided Reading Level: I.
470L
Decoding demand: 33 (low) Semantic demand: 60 (medium) Syntactic demand: 44 (medium) Structure demand: 80 (high)
Keywords: Racing -- Fiction; Swimming -- Fiction; African Americans -- Fiction